Sleep Dysregulation and Daytime Electrodermal Patterns in Children With Autism: A Descriptive Study. Issue 5 (3rd September 2021) - Chong, Pearlynne Li Hui; Abel, Emily; Pao, Ryan; McCormick, Carolyn E. B.; Schwichtenberg, A. J.
Abstract: Sleep deficiency influences emotion and behavior regulation but the mechanisms of influence are poorly understood. Emotion, behavioral, and sleep theories highlight differences in autonomic function as a potential pathway of influence and research in typical populations draw links between sleep deficiency and autonomic dysregulation (e.g., elevated reactivity within the sympathetic nervous system). In populations at elevated risk for sleep deficiency/problems (i.e., individuals with autism), greater variability in sleep and autonomic/arousal profiles may be particularly informative. Using electrodermal activity (EDA) as an indicator of sympathetic nervous system activation, this descriptive pilot study aimed to document daytime EDA patterns in children with autism and to explore their relations with sleep dysregulation/deficiency. EDA and sleep were measured using ankle and wrist worn sensors in 13 children (Meanage 6.11 years). EDA indices included nonspecific skin conductance responses (NSSCR) and tonic skin conductance levels (SCL). Descriptively, children in the dysregulated sleep group had fewer NSSCRs and lower SCL in the afternoon. This blunted physiological arousal profile/pattern is consistent with previous research, but this is the first study to explore how sleep may be linked. Notably, this pattern may not reflect sleep but an overall dysregulation profile which in this sample included: dysregulated sleep, a blunted afternoon arousal profile, and elevated ASD symptom severity. Replication with larger, more diverse samples is needed to disentangle the complex relations among sleep, arousal, and ASD behavioral features. However, this study represents an important first step in documenting extended daytime arousal patterns.